Epidemiological and genetic characterization of the influenza A (H1N1) virus in Hangzhou City in 2023 - Ningning Wang; Ningning Wang; Wei Lu; Li Yan; Mengru Liu; Mengru Liu; Feihu Che; Yue Wang; Chunli Yang; Mengyu Lv; Jun Cheng; Qingyang Sun; et al. (Frontiers Media S.A., 2024)
ObjectiveTo explore and describe the epidemiological and genetic variation characteristics of the influenza A (H1N1) virus in Hangzhou City.MethodsRespiratory throat swab specimens collected from the fever clinic of the 903rd Hospital of the Chinese People's Liberation Army (PLA) between January and March 2023 were collected. The respiratory pathogen antigens were identified using the colloidal gold method, and those testing positive for influenza A virus antigens were confirmed and subtyped by RT-qPCR. Seventeen H1N1 isolates were selected to amplify hemagglutinin (HA) and neuraminidase (NA) gene sequences via RT-PCR, and sequencing was completed following the identification of the amplified products. The sequenced HA and NA sequences were spliced using DNASTAR software (version 5.0), and a phylogenetic tree was constructed using MEGA software (version 11.0) for genetic characterization.ResultsA total of 2,376 respiratory samples were tested, with 680 cases testing positive for influenza A. Of these, 129 positive cases of influenza A were randomly selected for typing, resulting in the isolation of 112 H1N1 subtypes and 17 H3N2 subtypes. The HA genes of 17 strains of influenza A (H1N1) were randomly selected for amino acid homology comparisons with two vaccine strains recommended by the WHO for 2023 (A/Wisconsin/67/2022 (H1N1) and A/Victoria/4897/2022 (H1N1)). The HA gene results showed identities of 98.24 to 98.65% and 98.41 to 98.82%, respectively, and the NA gene results were 98.79 to 99.15% and 98.94 to 99.29%, respectively. Fourteen amino acid sites were altered in the HA gene of the 17 strains, with some strains contributing to the Sa and Ca antigenic determinants, respectively. Seventeen strains had mutations in the NA gene at sites 13, 50, 200, 339, 382, and 469. The sequenced strains, vaccine strains, and some 2023 domestic representative strains independently formed a branch 6B.1A.5a.2a.ConclusionThe continuous evolutionary mutations of the H1N1 virus genes in Hangzhou City suggest the possibility of the virus escaping from the immune response. This study provides an experimental basis for evaluating the protective effect of the vaccine and formulating preventive measures against influenza in Hangzhou City.